THE AXIOLOGICAL FEATURES OF ENGLISH AND UZBEK AGRONYMS - Xakimbayeva Ozoda kalandarovna (Modern American Journals, 2025)
This paper explores the axiological features of agronyms—place names related to agricultural environments such as fields, farms, settlements, and rural lands. While agronyms are often studied for their geographical and morphological properties, this study highlights their value-oriented (axiological) functions. Agronyms reflect societal attitudes toward labor, land, ecology, spirituality, and national identity. This analysis draws from both Uzbek and English toponymic materials to illustrate how agronyms embody and transmit cultural and moral values embedded in the linguistic worldview of rural communities.
Keywords: Agronyms, axiology, toponymy, linguistic values, rural culture, semantics, Uzbek, English.